Gambaran Sindrom Mata Kering pada Mahasiswa Fakultas Kedokteran Universitas Hang Tuah Angkatan 2018: Sindrom mata kering - RASYAD, CHICO MUHAMMAD; SAMSUDIN, MOH; PURWANINGSARI, DIAH (Universitas Hang Tuah, 2023)
Dry eye syndrome (DES) is a multifactorial disease of the ocular surface caused by hyperosmolarity of tears. Dry eyes can interfere with activities because it causes pain dan discomfort in the eyes. Gender and duration of gadget use are part of the risk factor for dry eye syndrome. This study was conducted with the aim of knowing the description of dry eye syndrome in students of the Faculty of Medicine Hang Tuah University Class of 2018. This type of study is descriptive. This research was conducted at the Faculty of Medicine, Hang Tuah University. The study was conducted from April 2021-November 2021. Data were obtained from online questionnaires on 154 students of the Faculty of Medicine, Hang Tuah University, Class of 2018. The sample was selected using simple random sampling method. The result showed that the severity of dry eye syndrome was 20.1% in the normal category, 19.5% in the mild category 22.1% in the moderate category and 38.3% in the severe category. In the male gender, 32.6% were found normal, 20.9% in the mild category, 16.3% in the moderate category and 30.2% in the sever category. In female gender, 15.3% were found in the normal category, 19.0% in the mild category, 24.3% in the moderate DES and 41.4% in the severe DES. The light duration of gadget usage shows 66.7% mild and 33.3% in the severe DES. The medium duration of gadget usage shows 30.7% normal, 15.4% in the mild DES, 38.5% in the moderate DES, 15.4 in the severe DES. The severe duration of gadget usage shows 19.6% normal, 18.8% with mild DES, 21,0% with moderate DES and 40,6% with severe DES. The conclusion of this study is the severity of DES is high, the female gender has higher prevalence of severity compared to male gender and the severe duration of gadget usage has a higher prevalence of severity. Keyword: Dry eye syndrome, severity, gender, duration of gadget usage